Engineered N-acetylhexosamine-active enzymes in glycoscience - Slámová, Kristýna; Bojarová, Pavla (Biochimica et biophysica acta. General subjects, 2017)
BACKGROUND: In recent years, enzymes modifying N-acetylhexosamine substrates have emerged in numerous theoretical studies as well as practical applications from biology, biomedicine, and biotechnology. Advanced enzyme engineering techniques converted them into potent synthetic instruments affording a variety of valuable glycosides. SCOPE OF REVIEW: This review presents the diversity of engineered enzymes active with N-acetylhexosamine carbohydrates: from popular glycoside hydrolases and glycosyltransferases to less known oxidases, epimerases, kinases, sulfotransferases, and acetylases. Though hydrolases in natura, engineered chitinases, β-N-acetylhexosaminidases, and endo-β-N-acetylglucosaminidases were successfully employed in the synthesis of defined natural and derivatized chitooligomers and in the remodeling of N-glycosylation patterns of therapeutic antibodies. The genes of various N-acetylhexosaminyltransferases were cloned into metabolically engineered microorganisms for producing human milk oligosaccharides, Lewis X structures, and human-like glycoproteins. Moreover, mutant N-acetylhexosamine-active glycosyltransferases were applied, e.g., in the construction of glycomimetics and complex glycostructures, industrial production of low-lactose milk, and metabolic labeling of glycans. In the synthesis of biotechnologically important compounds, several innovative glycoengineered systems are presented for an efficient bioproduction of GlcNAc, UDP-GlcNAc, N-acetylneuraminic acid, and of defined glycosaminoglycans. MAJOR CONCLUSIONS: The above examples demonstrate that engineering of N-acetylhexosamine-active enzymes was able to solve complex issues such as synthesis of tailored human-like glycoproteins or industrial-scale production of desired oligosaccharides. Due to the specific catalytic mechanism, mutagenesis of these catalysts was often realized through rational solutions. GENERAL SIGNIFICANCE: Specific N-acetylhexosamine glycosylation is crucial in biological, biomedical and biotechnological applications and a good understanding of its details opens new possibilities in this fast developing area of glycoscience.
Keywords: Glycoproteins; katalýza; Glycosyltransferases; Protein Engineering; Hexosamines; β-N-acetylhexosaminidase; Whole-cell engineering; proteinové inženýrství; Catalysis; Sulfotransferases; oligosacharidy; sulfotransferasy; glykosylace; hexosaminy; glykosidhydrolasy; Glycosylation; Chitinase; glykosyltransferasy; Glycoside Hydrolases; Glycosynthase; Oligosaccharides; Site-directed mutagenesis; glykoproteiny; Transglycosidase